Pelaksanaan Putusan Arbitrase Dalam Sengketa Antara Tiongkok Dan Filipina Di Laut Cina Selatan - Agnes Annora Nathania; Lestari, Maria Maya; Diana, ledy (Faculty of Law Universitas Lancang Kuning, 2024)
UNCLOS 1982 provides guidelines in the event of enforcement of international maritime law, one of which is Arbitration whose decision is final and binding. However, in practice, rejection and disobedience to arbitration decisions are not uncommon. In this study, the case of rejection of an arbitration decision occurred between China which rejected the decision of the Permanent Court of Arbitration filed by the Philippines against maritime rescue in the South China Sea region. This study aims to examine the legal force of arbitration decisions in enforcing maritime territory between the Philippines and China and the efforts that the Philippines can make against China's rejection of international arbitration decisions. The research method used in this study is normative legal research. Based on the research results, it can be concluded that first, the legal force of the arbitration award, in accordance with the nature of the arbitration award is final and binding and has binding legal force for the parties, especially China, because the submission of the settlement by the Philippines to the PCA is in accordance with the settlement procedure contained in UNCLOS 1982. Second, the efforts that can be made by the Philippines, the Philippines in dealing with China's rejection can prioritize diplomatic and negotiation methods rather than strict law enforcement, because success in resolving this settlement requires a comprehensive approach, involving collaborative efforts between the countries concerned and the international community as a whole.